Android-Based E-Business Marketplace Training to Improve MSMEs inTarumajaya Village - Ahmad Chusyairi; Ega Dioni Putri; Kevin Ananda Putra; Ikhwanul Hakim; Agung Riyadi (SWAGATI : Journal of Community Service, 2025)
This community service activity was motivated by the low level of digital literacy and the suboptimal use of online marketplaces by MSMEs in Tarumajaya Village, Bandung Regency. The objective of this activity was to enhance the community’s ability to develop and utilize Android-based e-business applications. The implementation method included the following stages needs analysis, training design, training delivery using Android Studio, mentoring and monitoring, and evaluation. Participants in the activity consisted of BUMDes managers and village SME operators. Prior to the activity, participants had limited understanding of digital marketing and had not yet implemented e-business systems. Following the training, there was an improvement in participants’ understanding and skills, demonstrated by their ability to create simple marketplace applications and use them for product promotion and transactions. Success indicators include improved digital literacy, successful application development, and increased business process efficiency. This initiative also had a positive impact on expanding market reach and the potential for increased revenue. In conclusion, Android-based e-business training is effective in enhancing digital competencies and supporting the transformation of village-based SMEs.